2021
DOI: 10.3390/antiox10040559
|View full text |Cite
|
Sign up to set email alerts
|

Cisd2 Protects the Liver from Oxidative Stress and Ameliorates Western Diet-Induced Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) and its more severe form, nonalcoholic steatohepatitis (NASH), are the most common chronic liver diseases worldwide. However, drugs to treat NAFLD and NASH are an unmet clinical need. This study sought to provide evidence that Cisd2 is a molecular target for the development of treatments targeting NAFLD and NASH. Several discoveries are pinpointed. The first is that Cisd2 dosage modulates the severity of Western diet-induced (WD-induced) NAFLD. Specifically, Cisd2 haplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…MitoNEET located in mitochondrial outer membrane was identified to function as an exporter of iron-sulfur clusters or iron between the cytoplasm and the mitochondria. CISD2 expression could protect the liver from oxidative stress, reduce the occurrence of mitochondrial DNA deletions, and protect the liver from the nonalcoholic fatty liver disease [33]. Sohn et al demonstrated that the NEET proteins were central to human breast cancer cells, and rendered them resistant to oxidative stress by mediating iron and ROS homeostasis in mitochondria [34].…”
Section: Discussionmentioning
confidence: 99%
“…MitoNEET located in mitochondrial outer membrane was identified to function as an exporter of iron-sulfur clusters or iron between the cytoplasm and the mitochondria. CISD2 expression could protect the liver from oxidative stress, reduce the occurrence of mitochondrial DNA deletions, and protect the liver from the nonalcoholic fatty liver disease [33]. Sohn et al demonstrated that the NEET proteins were central to human breast cancer cells, and rendered them resistant to oxidative stress by mediating iron and ROS homeostasis in mitochondria [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that Cisd2 plays an important role in maintaining a normal redox status [ 18 ]. To further analyze intracellular redox status and oxidative stress and evaluate the protective function of Cisd2 in the antioxidant defense during natural aging, we carried out Western blot analyses of liver extracts using antibodies targeting either cysteine S-sulfonation or tyrosine nitration.…”
Section: Resultsmentioning
confidence: 99%
“…By way of contrast, a persistently high level of Cisd2 in the Cisd2TG mice preserves mitochondrial function and protects the activity of Complexes I–V in the skeletal muscles of old mice [ 12 ]. Moreover, using the Western pattern diet-induced NAFLD, the levels of reactive species, including ROS and RNS, are significantly increased in the livers of heterozygous mice carrying hepatocyte-specific knockout of Cisd2 (Cisd2hKO+/–) while overexpression of Cisd2 alleviates the Western pattern diet-induced oxidative stress in Cisd2TG mice [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also maintained the structure of the liver and protected it from age‐related pathological damage (Huang, Shen, Huang, Lin, & Tsai, 2021). Several studies have identified that CISD2 played a protective role in fatty liver disease and spinal cord injury (Huang, Shen, Huang, Teng, et al, 2021; Kung et al, 2020). In addition, CISD2 alleviated hypoxia/reoxygenation‐induced oxidative stress and inflammatory responses in HT22 hippocampal neurons via the Akt‐Nrf2‐activated pathway (Ren et al, 2022).…”
Section: Discussionmentioning
confidence: 99%